The Effect of Information Technology and Facilitating Conditions on Audit Risk (Survey of Public Accounting Firms throughout Central Java) - Astuti, Dewi Saptantinah Puji; Mardayanti, Leni (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This study addresses the research gap concerning the factors influencing Audit Risk in Public Accounting Firms, particularly the limited empirical evidence on the roles of Information Technology and Facilitating Conditions. Audit risk arises when auditors issue inappropriate opinions on financial statements containing material misstatements, which can undermine financial accountability and stakeholder trust. This research investigates how Information Technology and Facilitating Conditions affect Audit Risk in Public Accounting Firms located in Central Java. Using a descriptive quantitative approach, data were collected via structured questionnaires from 60 purposively selected auditors with a minimum of three years of experience across various audit engagements. The variables measured include components of Audit Risk (Inherent Risk, Control Risk, Detection Risk), Information Technology (use of AI and cloud computing), and Facilitating Conditions (knowledge, resources, compatibility, and ease of use). Data analysis was performed using SPSS software, incorporating validity and reliability tests, as well as classical assumption tests such as normality, multicollinearity, autocorrelation, and homoscedasticity, followed by multiple linear regression analysis. The findings reveal that Information Technology has a negative but statistically insignificant effect on Audit Risk, while Facilitating Conditions exhibit a positive and significant influence. Collectively, both variables significantly impact Audit Risk. These results highlight the critical role of organizational support systems in mitigating audit risk, suggesting that improvements in facilitating conditions may be more influential than technology adoption alone in the context of auditing practices.